Dielectric focusing elements for integrated optics - JENNINGS, BRIAN DAVID (Trinity College Dublin. School of Physics. Discipline of Physics, 2018)
The ability to propagate light around a `circuit' on a single chip has an abundance of applications. Connecting different elements can bring huge functionality to a minuscule device---as evidenced by integrated electronic circuits. To make full use of the benefits afforded by integrated optical circuits, elements of different sizes and materials will need to be used. To do this, connections between relatively large waveguides and sub-micron elements and vice-versa will be made. In this thesis, the propagation of light in multi-mode waveguides is presented; these waveguides form the connections between the different elements. Dielectric focusing elements, used to decrease the beam width as it moves from one element to another are also discussed. The different structures are studied through simulation and experiment. The focusing elements operate in different regimes: one a structure separate from the waveguide, gathering the light radiated from the end-face of the waveguide; the other a perturbation of the core of the waveguide, redirecting the light propagating through it. The dielectric focusing elements were initially intended as couplers to more powerful plasmonic focusing elements but can find use in a host of applications.
APPROVED
Keywords: Dielectric waveguides; Dielectric focusing elements; Optics